In the grip of Grace: Henri Nouwen’s perspectives on the Unitive stage of the Mystical path - Marchinkowski, George (Stellenbosch Theological Journal, 2022)
This article will consider the unitive stage in the mystical path Henri Nouwen lived and wrote about. It will begin by characterising the mystical way, together with its journey motif. Then, it will place Nouwen's spirituality within the context of his life and writing, and finally, it will outline three events which led Nouwen to describe the unitive stage of the mystical journey tentatively. The first "mystical moment" emerges from Nouwen's contemplation of the Divine/Human embrace in Rembrandt's painting, The Return of the Prodigal Son. The second occurs as a result of his reflection on the spiritual significance of attending to the practical needs of a severely disabled man, and the third from his contemplation on a flying trapeze performance at a circus. The article proposes that these encounters were mystical, came as a result of Nouwen's contemplative practice, and shaped Nouwen's perception of the unitive stage in his mystical journey.